Analisis Performa Alat Planishing Hammer Melalui Metode Elemen Hingga Dan Eksperimen - Sugianto, Irwan; Afrizal, Efi; Arief, Dodi Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Planishing hammer is a tool for plate forming with a utilizing impact force that happened as a result of hammer’s impact. This research was conducted to find the performance of planishing hammer, then do some methods to get value of force that happened. As for the method used are manual calculation, experimental, and simulation. Simulation method was done by Finite Element Method (FEM) concept using commercial software, collusion Abaqus. The experiment performed with metal formed to plate, where at planishing hammer pasted a strain gauge that activated by microcontroller and used Arduino UNO which can be connected directly to a computer to see the stress that happened to hammer. The experiment was conducted to get the maximum force of forwarded from electric motor ¼ HP with principle of power transmission utilizing eccentric shaft for until the plate is deformed. For manual calculation was used mechanism 4 bars, wherein the linear velocity were calculated by analytic methods. Based manual calculation method, the value of  force 2413.86735 N. By experimental method thrice, the value of force are 2748.081 N,  2775.518 N and 2742.478 N, and with simulation the value of force is 2165.961 N. Keywords: Plate, Software, Strain Gauge, Maximum force, Deformation